Understanding food safety certification: key determinants, barriers, and antecedents - Mohd Shahir, Omar; Muhammad Fakhrul, Yusuf; Cheng, Jack Kie (Lembaga Pemasaran Pertanian Persekutuan (FAMA), 2024)
This study aims to identify the elements influencing food safety certification adoption and conduct a thematic analysis using the Technology-OrganizationEnvironment (TOE) framework and eco-innovation principles to determine focus areas for stakeholders. A comprehensive literature search was conducted, followed by thematic analysis based on four themes: technology, organization, environment, market pull, and regulation pull/push. The review identified 33 key elements related to food safety certification adoption, classified into three categories: 12 determinant elements driving adoption, 9 barrier elements representing challenges faced by farmers, and 12 antecedent elements as pre-existing conditions influencing adoption. The findings reveal that market pull is a dominant determinant, significantly influencing certification adoption, while regulation pull/push factors emerge as the most significant barriers. Furthermore, organizational factors play a crucial role in the successful adoption of food safety certification among producers. Based on these insights, stakeholders, including policymakers and farmers, should prioritize addressing barriers while reinforcing drivers of certification adoption. Streamlining regulatory frameworks and creating incentives for small-scale producers will enhance accessibility and support. Increasing consumer awareness and strengthening internal organizational capacities through targeted training programs can further promote certification practices. However, this study acknowledges several limitations, including the potential variability of thematic elements across regions, which may affect the applicability of the findings. Future research should gather expert opinions on identified elements, explore regionspecific influences, and examine the long-term impact of certification on farm profitability and market competitiveness to foster sustainable certification adoption.